Hypertriglyceridemia-Associated Drug-Induced Acute Pancreatitis. Issue 1 (January 2019) - Elkhouly, Mohamed A.; Salazar, Miguel Jose; Simons-Linares, Carlos Roberto
Abstract : Objectives: The aim of our study was to investigate the cases of drug-induced acute pancreatitis (DIAP) with hypertriglyceridemia as the mechanism of injury. Methods: A MEDLINE search (1963–2018) of the English language literature was performed looking for all human case reports of adults (>18 years old) with hypertriglyceridemia as the mechanism of DIAP. The latest search date was February 28, 2018. Drugs were classified into probability groups based on a classification used by Badalov et al ( Clin Gastroenterol Hepatol . 2007;5:648–661). Results: The search revealed a total of 76 cases in 59 published reports. A total of 25 medications were found to be implicated in DIAP secondary to hypertriglyceridemia mechanism. Most of acute pancreatitis cases were mild or moderately severe with favorable outcomes. In 3 cases involving tamoxifen, pagaspargase, and quetiapine, patient death was the outcome. Plasmapheresis was only used in 9 cases in an effort to decrease triglyceride levels. Conclusions: Hypertriglyceridemia-associated DIAP is a rare phenomenon, and the current systematic review provides a summary of drugs that have been implicated in this phenomenon, which allow physicians to be oriented about this adverse effect when these drugs are used.